Regional Localization of Loci for Human PGM(1) and 6PGD on Human Chromosome One by Use of Hybrids of Chinese Hamster-Human Somatic Cells - Douglas, George R. (1973)
The human gene loci phosphoglucomutase(1) (PGM(1), EC 2.7.5.1) and 6-phosphogluconate dehydrogenase (6PGD, EC 1.1.1.43), which are located on human chromosome one, have been assigned to a specific region of the short arm of that chromosome, by use of a hybrid cell line derived from a Chinese hamster cell line deficient in hypoxanthine phosphoribosyl transferase and a strain of human diploid fibroblasts. Cytogenetic analysis of a hybrid clone maintained for about 50 generations in vitro revealed two populations of cells, the first containing a human chromosome one with a break point at band 1p33, such that about 25% of the short arm of this chromosome was deleted. The second cell population contained a normal chromosome one. Biochemical analysis of subclones derived by cloning this mixed population revealed two phenotypic classes, one of which expressed all three chromosome-one markers, PGM(1), 6PGD, and peptidase C (Pep C), while the other expressed only Pep C. Cytogenetic analysis showed that the subclones expressing all three markers carried the normal human chromosome one, while those expressing only Pep C carried the deleted chromosome. These data indicate that the human gene loci PGM(1) and 6PGD are located on the short arm of chromosome one distal to the break point, while Pep C lies elsewhere on the chromosome.